(untitled) (Papeles, 2017)
The comparative analysis between the conceptions and uses of punctuation used by students makes possible to understand why the acquired knowledge about its rules in the educational field is not reflected in their textual practices. In this way, this paper aims to become an exhortation to rethink the elements that permeate the writing processes according to the punctuation marks in order to enable a strengthening in them; thus it is an epistemic recognition of relation among thinking, writing and punctuation. For this, a case study was carried out with 10th grade students from Colombo Florida Bilingual School, which allowed it to account for the phenomenon presented here.